The Effect Of Smk3 Implementation, Safety Culture And Project Leadership On Ohs Performance In Construction Projects In Dili City, Timor Leste - Pedro Maria Lopes Pacheco; Anton Soekiman; Chandra Afriade Siregar (J-ENSITEC (Journal of Engineering and Sustainable Technology), 2026)
The construction industry is widely recognized as one of the sectors with the highest levels of occupational risk, particularly in developing countries such as Timor Leste. The implementation of the Occupational Health and Safety Management System (OHSMS/SMK3) in construction projects is often limited to administrative compliance and is not fully supported by a strong safety culture and effective project leadership, resulting in suboptimal Occupational Health and Safety (OHS) performance. Therefore, understanding the interaction among these factors is essential to improving safety outcomes in construction environments. This study aims to analyze the influence of OHSMS implementation, safety culture, and project leadership on OHS performance in construction projects located in Dili City, Timor Leste. The research also examines both direct and indirect relationships among variables, including the mediating role of safety culture and OHSMS implementation. A quantitative research approach was employed using a survey method, in which structured questionnaires were distributed to construction project personnel directly involved in OHS activities. The collected data were analyzed using the Partial Least Square–Structural Equation Modeling (PLS-SEM) technique to evaluate the measurement and structural models. The findings reveal that OHSMS implementation and safety culture have significant positive effects on OHS performance. Project leadership demonstrates a crucial role in strengthening safety culture and enhancing the implementation of OHSMS, while also exerting an indirect influence on OHS performance through these mediating variables.  Overall, the results emphasize the importance of integrating systematic, cultural, and leadership approaches to achieve sustainable improvements in occupational health and safety performance within construction projects in Timor Leste.